(3GdMQcI GdhWfjI GdLRGFQjI (B/s - (3CHh GdbGSe, SYO Gddgs ((3HjQhJ (B:s (3efThQGJ OGQ GdBOGH ,s, 1969)
(3gPg JQLeI dGWQhMI GdOcJhQGg GdJj MUd HgG GdeDda Ydi GdOcJhQGg aj GdJGQjN h GdYdhe GdSjGSjI ef LGeYI ejfjShJG HCejQcGs
Keywords: (3GdeSGhGI s; (3GdfgVI s; (3XghQ GdCMRGH GdSjGSjI s; (3GdMQcI GdhWfjI s